Romania : Ex-Post Assessment of Longer-Term Program Engagement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper reviews the experience of the IMF's long-term engagement in Romania and options for future IMF involvement. The unfavorable growth performance also reflected adverse conditions for private sector development. Foreign investors have welcomed the more stable macroeconomic environment and the tax legislation overhaul under the recent Stand-By Arrangement. Although the overlap between Bank and IMF conditionality in the area of structural reforms was not conducive to reducing the number of conditions, it helped increase the pressure on the authorities to maintain the reform momentum.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet